Study Minat Berkunjung Ulang di Kota Lama Semarang dengan Daya Tarik, Fasilitas dan Kepuasan Wisatawan sebagai Prediktornya - Trenggono Trenggono; Andhi Supriyadi (Mahesa Research Center, 2024)
This study aims to analyze the impact of tourist attraction and facilities on tourist satisfaction and its effect on revisit intention in Kota Lama Semarang. A quantitative approach with survey methods and statistical data analysis was employed to identify the relationships between these variables. The findings indicate that tourist attraction and facilities positively influence revisit intention, with tourist satisfaction serving as a significant intervening variable. Enhancements in tourist attractions, such as themed events and performances, and improvements in facilities, such as establishing supermarkets and increasing visitor comfort, were found to boost tourist satisfaction and subsequently, revisit intention. Tourist satisfaction emerged as the dominant factor influencing the decision to revisit. Based on these findings, it is recommended to organize more engaging events, improve supporting facilities, and provide comfortable dining areas as strategies to attract and retain tourist interest. Implementation and evaluation of these recommendations can be conducted through visit data analysis and tourist satisfaction surveys to assess the effectiveness of the applied strategies.